Ethical indications for radiological procedures: a clearer picture. (20th March 2012) - Clement, Rhys Gareth Ellis
Abstract : An 80-year-old gentleman presented with long-standing diarrhoea and weight loss. A large bowel malignancy was suspected but his co morbidity precluded major abdominal surgery. At the time of treatment CT colonography was not in common use and the investigation of choice was barium enema. Due to the invasive nature of this procedure the medical team decided it would not be in his best interests to subject him to further investigation. Uncertainty surrounding his diagnosis was distressing for him and his family who felt that a firm diagnosis would allow them to plan his ongoing care needs. The patient accepted the risks and underwent a barium enema that confirmed the presence of a large bowel carcinoma that was inoperable. The case highlights how application of the ethical principles can aid the decision making process in difficult scenarios and emphasises the importance of treating the individual and not the disease.